2020
DOI: 10.9734/jpri/2020/v32i1630741
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness on Personalized Medicine amongst Health Care Specialists and University Students in Health Colleges in Saudi Arabia

Abstract: Aim: There are a few studies about the populations' knowledge and perceptions on personalized medicine in Saudi Arabia until now. Therefore, the aim of this study was to assess the knowledge and awareness on personalized medicine amongst health care specialists and university students in health colleges in Saudi Arabia. Methodology: This is a cross-sectional study that include a survey targeting health care specialists. The survey translated to Arabic and after validation, it was converted to an online s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
2
10
2
Order By: Relevance
“…In a further recommendation, additional training and awareness programs are required to raise health care providers' understanding of personalized medicine and to assist its implementation in Saudi Arabia. More emphasis on this topic should be put into the curricula of health colleges 17 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a further recommendation, additional training and awareness programs are required to raise health care providers' understanding of personalized medicine and to assist its implementation in Saudi Arabia. More emphasis on this topic should be put into the curricula of health colleges 17 …”
Section: Discussionmentioning
confidence: 99%
“…An interesting study reported that HCPs have limited awareness about personalized medicine in general, but have positive attitudes toward it and are keen and eager to learn more about personalized medicine for future practice. 17 In a further recommendation, additional training and awareness programs are required to raise health care providers' understanding of personalized medicine and to assist its implementation in Saudi Arabia. More emphasis on this topic should be put into the curricula of health colleges.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations